Influencia del tiempo de almacenamiento de huevos, en gallinas reproductoras de la línea Cobb-500, previo a la incubación, sobre los parámetros de incubabilidad - Reyes Chávez, Luis Enrique (2019)
The present investigation: Influence of the time of egg storage, in reproductive hens of the Cobb-500 line, previous to the incubation, above the incubability parameters, was developed in the "Rodríguez" SAC Incubation Plant, with a duration of three months, whose objective was to determine the influence of egg storage time, prior to incubation, on hatchability parameters. For this study, 280 fertile eggs were used from batch 4B of breeding hens of the Cobb 500 line of the same hatchery. The Completely Random Design was used with four treatments and two repetitions. Each experimental unit was represented by a group of 70 eggs. The treatments were: T0 (Fresh eggs), T1 (1-3 days of storage), T2 (3-5 days of storage), T3 (5-7 days of storage). As for the results obtained, regarding moisture, the highest loss corresponds to treatment two, with 13.72%; the highest fertility was obtained in treatment three, with 98.57%; the highest hatchability was achieved in treatment three with 92.86%; the highest proportion of first quality chicks was obtained in treatment three, with 65 BB chicks; the highest embryonic mortality was found in the incubation of fresh eggs, with 10%; the greater weight of the chick BB corresponds to treatment one, with 49 grams. It is concluded that the storage time of the eggs does not influence the parameters of hatchability, since the eggs stored for seven days gave high percentages. Finally, based on these results, under conditions similar to those of the present study, it is recommended to store the eggs until 7 days.